Co‐Dissolved Isostructural Polyoxovanadates to Construct Single‐Atom‐Site Catalysts for Efficient CO2 Photoreduction. Issue 6 (28th December 2022) - Wang, Yu‐Jie; Zhuang, Gui‐Lin; Zhang, Jiang‐Wei; Luo, Fang; Cheng, Xin; Sun, Fu‐Li; Fu, Shan‐Shan; Lu, Tong‐Bu; Zhang, Zhi‐Ming
Abstract: We explored a co‐dissolved strategy to embed mono‐dispersed Pt center into V2 O5 support via dissolving [PtV9 O28 ] 7− into [V10 O28 ] 6− aqueous solution. The uniform dispersion of [PtV9 O28 ] 7− in [V10 O28 ] 6− solution allows [PtV9 O28 ] 7− to be surrounded by [V10 O28 ] 6− clusters via a freeze‐drying process. The V centers in both [PtV9 O28 ] 7− and [V10 O28 ] 6− were converted into V2 O5 via a calcination process to stabilize Pt center. These double separations can effectively prevent the Pt center agglomeration during the high‐temperature conversion process, and achieve 100 % utilization of Pt in [PtV9 O28 ] 7− . The resulting Pt‐V2 O5 single‐atom‐site catalysts exhibit a CH4 yield of 247.6 μmol g −1 h −1, 25 times higher than that of Pt nanoparticle on the V2 O5 support, which was accompanied by the lactic acid photooxidation to form pyruvic acid. Systematical investigations on this unambiguous structure demonstrate an important role of Pt−O atomic pair synergy for highly efficient CO2 photoreduction. Abstract : Dispersing nanosized [PtV9 O28 ] 7− clusters into a [V10 O28 ] 6− aqueous solution, the so‐called co‐dissolved strategy, ensures double separations resulting in the construction of Pt single‐atom catalysts (SACs). The SAC with Pt/O synergism can efficiently boost CO2 photoreduction.